Analysis of Stock Portfolio Performance Using Passive Strategy and Active Strategy with Single Index Model - Ricki (Indonesian Development of Economics and Administration Journal, 2023)
This study aims to determine and analyze the differences in return and risk performance results of active portfolio strategies and passive portfolio strategies using the Single Index Model. Then measure the return performance using the Sharpe Index, Treynor, and Jensen's Alpha. This research was conducted on Sri-Kehati index stocks for the period November 2019 to November 2021. Based on passive portfolio strategy research, there are three stocks that form the optimal portfolio, namely PT Bank Central Asia Tbk (BBCA), PT Japfa Comfeed Indonesia Tbk (JPFA), and PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO). While based on active portfolio strategy research, in the first year there were three stocks that formed the optimal portfolio, then in the second year there were four stocks forming the optimal portfolio, namely PT Dharma Satya Nusantara Tbk (DSNG), PT Vale Indonesia Tbk (INCO), PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO), and PT Wijaya Karya (Persero) Tbk (WIKA). Based on performance measurement using Sharpe, Treynor and Jensen's Alpha indices, the Passive Portfolio Strategy is better than the Active Portfolio Strategy. Meanwhile, based on the difference test using the Mann Whitney U test method, it can be concluded that there is no significant difference in return performance between passive portfolio strategies and active portfolio strategies..